Significance of the Neutrophil-to-Lymphocyte Ratio in p16-Negative Squamous Cell Carcinoma of Unknown Primary in Head and Neck - Xu, Chunmiao; Yuan, Junhui; Du, Wei; Wu, Junfu; Fang, Qigen; Zhang, Xu; Li, Hailiang (Frontiers in Oncology, 2020)
Objective: The neutrophil-to-lymphocyte ratio (NLR) has been reported to be associated with survival in solid malignancies. The main goal was to evaluate the prognostic significance of the NLR in patients with p16-negative squamous cell carcinoma of unknown primary (SCCUP) in head and neck. Methods: The association between the NLR and clinical pathologic variables was evaluated by the chi-square test. The primary endpoint of interest was disease-specific survival (DSS). Univariate and Cox model analyses were used to evaluate prognostic factors. Results: A total of 153 patients were included in the analysis. Cancer cachexia was noted in 10 patients. The mean NLR value was 3.9 (range: 1.4-8.3). A high NLR was significantly associated with cancer cachexia development. The 5-year DSS rate was 58%. In patients with NLRs varying from 1.4 to 3.7, the 5-year DSS rate was 71%; in patients with NLRs varying from 3.7 to 6.0, the 5-year DSS rate was 57%; in patients with NLRs varying from 6.0 to 8.3, the 5-year DSS rate was 39%, and the difference was significant (p=0.001). Further Cox model analysis confirmed the independence of the NLR in predicting survival. Conclusions: In patients with p16-negative SCCUP, an NLR ≥6.0 is significantly associated with worse prognosis.